1999
DOI: 10.1046/j.1523-1755.1999.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mortality in ESRD patients on convective and diffusive extracorporeal treatments

Abstract: These results support the hypothesis that convective treatments are associated with a nonsignificant trend toward better survival and significantly delay the need for CTS surgery. An older age and the presence of diabetes and heart disease are other important risk factors for CTS surgery. These results could have an important clinical impact given the relevance of DRA in dialysis patient morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(128 citation statements)
references
References 27 publications
3
118
0
7
Order By: Relevance
“…Enhanced middle molecule clearance has other benefits. Previous studies demonstrated improved ␤2-microglobulin clearance by HDF (11,25,26), and one retrospective study suggested that convective dialysis treatments reduce the incidence of carpal tunnel syndrome (27).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced middle molecule clearance has other benefits. Previous studies demonstrated improved ␤2-microglobulin clearance by HDF (11,25,26), and one retrospective study suggested that convective dialysis treatments reduce the incidence of carpal tunnel syndrome (27).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The results of previous studies that evaluated the possible clinical advantages of HDF in comparison with HD are not consistent, and it is not possible to make any precise conclusion out of them. [17][18][19][20][21] Compared with low-flux dialysis, high-flux HD might have a beneficial effect on mortality and clinical outcomes in the patients [22][23][24][25][26][27] or not. 28 The use of synthetic high-flux membranes should be considered to delay the longterm complication of HD therapy: amyloidosis, hyperphosphatemia, cardiovascular risk, and anemia.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Observational studies have consistently suggested that high-flux treatments for long-term dialysis patients with stage 5 CKD are associated with reduced morbidity and mortality. [5][6][7][8] The Hemodialysis (HEMO) Study, 9 a landmark randomized, controlled trial designed to test the effect of membrane flux and dialysis dosage on mortality, showed that high-flux HD is associated with a nonsignificantly lower relative mortality risk of 8%, although a secondary analysis suggested a significant advantage of highflux membranes in patient subgroups. More recently, the Membrane Permeability Outcome (MPO) study 10 found that survival could be significantly improved by using high-flux as compared with low-flux membranes in high-risk patients identified by serum albumin of Յ4 g/dl as well as in patients with diabetes in a post hoc analysis.…”
mentioning
confidence: 99%